Research Culture of Public Schools in Tagbilaran City, Bohol - Mangana, Jhema Faith S. (Future Science / FSH-PH Publications, 2022)
DepEd strives to promote and strengthen the culture of research in basic education. Along with this goal, this study aimed to determine the research culture and to recognize the extent of influence of the factors on research culture of public schools in Tagbilaran City, Bohol. It employed a quantitative descriptive research design with a survey questionnaire as the main instrument to gather the data needed in the study. Two instruments were utilized and modified in this study adapted from The Factors Influencing the Research Culture by Iqbal and colleagues and the Research Culture and Productivity of the Faculty of Accredited Private Higher Education Institutions by Tagaro. These were administered to 254 public school teachers as respondents from 25 public schools in DepEd Tagbilaran City Schools Division. Findings revealed a moderate influence on the extent of influence of the factors on research culture of Tagbilaran City public schools. Among the factors, Environmental Factor had a greater influence whereas Personal Factor had a lesser influence on the research culture. There was no significant relationship between the teachers’ selected profile and the extent of influence on research culture however sex, designation, and highest educational attainment affect the research productivity level. Moreover, data showed that there was no correlation between the extent of influence of the factors on research culture and research productivity level of the teachers.